Accellion vulnerabilities lead to breaches of major organisations. Issue 3 (March 2021) - Unknown
Abstract : Zero-day flaws in Accellion's File Transfer Appliance (FTA) product have resulted in breaches at major government and private organisations, some of which have led to significant compromises of data.